Reintegrating Philosophy More Effectively Into Initial Teacher Education - Zrudlo, Ilya (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2025)
The role of philosophy has gradually been minimized in initial teacher education (ITE) despite the benefits it can bring to teachers. One of the reasons it has been marginalized is because of the way it was being offered. I outline some relatively neglected critiques R. S. Peters laid out against the historical survey method of teaching philosophical foundations, as well as some of his suggestions for how to integrate philosophy of education into ITE. Backed up by more recent proposals by philosophers of education, I argue that some of Peters’ suggestions could help address some of the pressing challenges facing teacher education today. I then consider how these suggestions could be incorporated into a philosophical foundations course for ITE. I argue that setting in motion and maintaining a learning process about more effective ways of integrating philosophy into ITE would help us make the case for its meaningful (re)introduction.